Using Information and Communication Technologies to Promote Healthy Aging in Costa Rica: Challenges and Opportunities - Castro Rojas, María Dolores (2016)
Forma parte de los trabajos presentados para el Second International Conference, ITAP 2016, Held as Part of HCI International 2016 Toronto, ON, Canada, July 17–22, 2016